“Analisis Faktor-Faktor yang Berpengaruh terhadap Kepatuhan Wajib Pajak dengan Sikap Wajib Pajak atas Sanksi dan Denda sebagai Variabel Moderating (Studi Empiris Pada UMKM di Semarang Selatan)” - Sutikni Sutikni; Heru Sulistiyo (Jurnal Akuntan Publik, 2023)
This study was conducted to determine the factors that affect tax payer compliance in Semarang such as taxation awareness, taxpayer motivation, taxpayer's economic level and attitudes of tax payers on the implementation of sanctions and fines on UMKM in Semarang.The population in this study is Mandatory UMKM in South Semarang active as many as 74 UMKM consisting of 6 area data obtained from the Department of Cooperatives and UMKM in Semarang. The sampling method was conducted by census method, that is the amount of tax payer population of UMKM in South Semarang was all used as sample in this research. The results showed there was a significant and positive influence between the consciousness of taxpayers have a positive effect on taxpayer compliance. partially there is no significant and negative influence between tax payer motivation has a positive effect on tax payer compliance, partial there is a significant and negative influence between the tax payer's economic rate have a positive effect on tax payer compliance, partially there is no significant and negative influence between mandatory attitude the tax on fine sanction strengthens the influence of taxpayer's awareness of taxpayer compliance, partially there is no significant and positive influence between taxpayer's attitude on the implementation of fine sanction strengthens the influence of taxpayer motivation on taxpayer compliance, there is no significant and positive influence between attitude the taxpayer on the fine sanction strengthens the influence of the taxpayer's economic level on taxpayer compliance.